Investigating Effects of Nano/SBR Polymer on Rutting Performance of Binder and Asphalt Mixture - Mahmoud Ameri; Mostafa Vamegh; Hamed Rooholamini; Farshad Haddadi (Advances in Materials Science and Engineering)
Rutting is one of the most common distresses in flexible pavements and can affect vehicle controlling features. Although asphalt binder constitutes a small percentage of the asphalt mixture, its properties play a crucial role in pavement performance and its rutting resistance. One way of improving binder properties and rutting resistance is to use additives. In this research, nanoclay and SBR polymer have been simultaneously used to modify 60–70 penetration binder to study rutting resistance of binder and asphalt mixture. To this end, the storage stability, rotational viscosity, DSR, and RCR tests on binder and marshal stability were performed, and dynamic creep and wheel track tests on asphalt mix were performed to assess rutting performance. The test and statistical analysis results indicated that nanoclay has considerably positive impact on rutting and elastic deformation of neat and SBR-modified asphalt binder and mixture.